Academic Philosophy as a Way of Life - Kramer, Eli; Faustino, Marta; Telo, Hélder (Eidos. A Journal for Philosophy of Culture, 2024)
Preview: Over the past few decades, the idea of philosophy as a way of life (PWL) has gained undeniable prominence in contemporary debates about the nature and function of philosophy. Pierre Hadot forged the notion to denote the specific way in which ancient philosophers conceived of and practiced philosophy, stressing its performative character and its potential for self-transformation on the basis of what he called “spiritual exercises.” Referring primarily to the Hellenistic and Roman eras, Hadot claimed that “philosophy was a mode of existing-in-the-world, which had to be practiced at each instant, and the goal of which was to transform the whole of the individual’s life. Furthermore, he also implied that some modern and contemporary philosophers came close to this model of philosophical practice and described it as his own metaphilosophical ideal. As he comments in the same text: “Such is the lesson of ancient philosophy: an invitation to each human being to transform himself. Philosophy is a conversion, a transformation of one’s way of being and living, and a quest for wisdom.” This normative and pedagogic component is a crucial aspect of Hadot’s account of PWL. Indeed, Hadot is not just describing what philosophy was in the past, but also evaluating what it is in the present and considering what it could become beyond his (and our) time. This is one of the reasons that made his approach so popular and led to so many fruitful developments in the field of PWL. Inspired by Hadot’s account, which was complemented by the late Foucault’s own reflections on philosophy’s practical and performative potential, recent scholarship has characterized PWL as a metaphilosophical model that can be fruitfully used to criticize current academic practices and to develop innovative methodological approaches to the study, research, and teaching of philosophy, which in turn might enable a transformation of philosophical practices in the context of modern universities.